Menghitung Debit Air Limpasan di Pit Bukit Everest PT. Antam Tbk UBPN Sulawesi Tenggara - Heri Prabowo; Aulia Mutiara C (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Antam Tbk. Southeast Sulawesi UBPN is a state-owned enterprise engaged in the mining and nickel ore processing sector which has an IUP area located in Pomalaa District, Kolaka Regency, Southeast Sulawesi Province. The mining front area consists of 4 regions, namely the northern mine, the central mine, the southern mine, and Maniang Island with a mining area of 6324 hectares. The mining method applied by PT. Antam Tbk. Southeast Sulawesi UBPN is openpit and open cast.Based on guidance from supervisors, Everest Pit is the biggest Pit compared to Pit Wrangler and Pit Rubicon. Sampling is carried out after high rainfall. At each Mining Front, runoff water is very influential on mining activities. Which if not done earlier prevention, will result in all mining activities stopped.After an analysis of the Bukit Everest Pit discharge, the discharge value obtained in each of the catchment areas, namely DTH 1 with value of 11.32, DTH 2 was 4.31 m³ / sec and DTH 3 was 1.50 m³ / sec.Key Word : Catchmen area, open pit, open cast, pit